MORPHOLOGICAL CHANGES IN THE GALL BLADDER AND BILIARY SYSTEM IN ACUTE AND CHRONIC CHOLECYSTITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This research explores the morphological changes observed in the gall bladder and biliary system during acute and chronic cholecystitis. Cholecystitis is a significant medical condition characterized by inflammation of the gall bladder, leading to structural and functional impairments. The study investigates the histopathological and imaging findings associated with these conditions, providing a comprehensive understanding of their progression. By analyzing various patient cases and reviewing relevant literature, the research identifies critical markers and morphological alterations that aid in diagnosis and treatment.